Modern methods of vertical malocclusions' treatment in the period of permanent dentition - Trokhimets, Yulia; Rashchenko, Natalia (The Ukrainian Scientific Medical Youth Journal, 2026)
malocclusions are the most common diseases of the maxillofacial area, which requires the special attention to the issues of their timely diagnosis, effective prevention and treatment. Vertical malocclusions in the period of permanent dentition during clinical examination are diagnosed for 21-40% of examined, and their main types - deep and open bite - significantly affect the level of dental and general health, that determines the average and high level of necessity for orthodontic treatment. The purpose of this article is to investigate scientific sources on the effectiveness of various treatment methods and methods of stabilizing the obtained results after treatment of vertical malocclusions in the period of permanent dentition over the past 10 years. 52 scientific sources from the databases Scopus, PubMed, Google Scholar were processed. Treatment of vertical malocclusions in the period of permanent dentition (especially open bite) is difficult and technological. Long-term active and retention periods are the specific features of treatment. Among the leading methods of this pathology type`s treatment, myotherapeutic, appliance-based, surgical, prosthetic and complex methods are distinguished. Myofunctional therapy is aimed at restructuring pathological muscle reflexes and establishing new muscle patterns which eliminate bad habits. The strategies of open and deep bites appliance-based treatment have a number of differences. While treating open bite of adult patients, removable and non-removable appliances are used to extrude incisors, intrude molars and premolars, change the position of the lower jaw, etc.; when correcting a deep bite, the process of incisors intruding, their proclination, extruding molars is being executed, or there is a combination of these methods during treatment. High efficiency of surgical methods (orthognathic surgery, usage of microimplants, microscrews, temporary anchorage devices) in the complex treatment of vertical malocclusions in the period of permanent dentition has been established. Thus, vertical malocclusions during the period of permanent dentition are an urgent problem of modern orthodontics, that is determined the development of new accessible and effective treatment algorithms. At the same time, data on the advantages of individual treatment methods are contradictory and require further research. A perspective direction for improving treatment tactics is the study of new combined treatment methods which affect the main links of etio- and pathogenesis, that provides a long-term therapeutic effect in the future. The improvement of the process for the passive stage of orthodontic treatment must be carefully considered.